Analysis on the Vertical Additional Force of Shaft and Drainage Settlement Characteristics of Topsoil Containing Multiaquifers. (25th July 2022) - Han, Tao; Luo, Tingting; Zhang, Tao; Yan, Yong; Hu, Xiaoxu; Yan, Tao; Yang, Weihao
Abstract : The vertical additional force induced by the drainage consolidation settlement of the topsoil is one of the main factors for shaft wall fracture. To date, the number of aquifers of topsoil rises with the depth increasing of shaft, which would lead to a more serious additional force effect. Thus, studying the vertical additional force law of the shaft when drainage settlement occurs in its surrounding topsoil containing multiaquifers is of great significance to predicting the shaft stress and guarantying shaft safety. In this study, mechanical analysis of the topsoil with the shaft crossing multiaquifer was carried out, and the settlement of each aquifer and aquiclude was calculated by separating the single-slope drainage consolidation and the double-slope drainage consolidation. Then, the calculation model of vertical additional force was established due to the settlement caused by the reaction of the additional force on the topsoil containing multiaquifers, and the calculation model of shaft wall stress was also developed. Verification of this model was conducted by comparing the filed measurement data of the shaft wall strain and the theoretical data calculated by the stress model. Finally, the effect laws of drainage velocity, central aquifer thickness, location, and number on the additional force were obtained and analysed. This paper is expected to provide theoretical support for predicting the additional force and shaft wall stress during its service time.